Pilgrims & Sultans : The Hajj Under the Ottomans - Faroqhi, Suraiya, 1941- (London I.B. Tauris, 2014)
Overview The pilgrimage to Mecca - the hajj - is a major aspect of the Islamic religion, yet little has been written about its history or of the conditions under which thousands of pilgrims from far flung regions of the Islamic world traveled to the heart of the Arabian peninsula. This pioneering book concentrates on the pilgrimage in the sixteenth and seventeenth centuries, when Mecca was ruled by the Ottoman sultans. At a time when, for the majority of the faithful, the journey was long, arduous and fraught with danger, the provision of food, water, shelter and protection for pilgrims presented a major challenge to the provincial governors of the vast Ottoman Empire. Drawing on rich documentation left by Ottoman administrators and on the accounts of contemporary pilgrims, Suraiya Faroqhi here sheds new light on the trials and experiences of everyday life for those undertaking the hajj.
Include Index
Keywords: Muslim pilgrims and pilgrimages -- Saudi Arabia--Mecca